Halloween mice! - Roberts, Bethany; Cushman, Doug (New York : Clarion, 1995)
Mice whirling and skipping on Halloween night are threatened by an approaching cat, until they come up with a scary trick to defend themselves.
Elem. School Library Collection
School Library Journal
Publisher's Weekly
1.5
K-3
Keywords: Mice -- Fiction; Cats -- Fiction; Halloween -- Fiction; Mice -- Fiction; Cats -- Fiction; Halloween -- Fiction